![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
x^5+x^4+1=x^5+x^4+x^3-x^3-x^2-x+x^2+x+1=x^3(x^2+x+1)-x(x^2+x+1)+x^2+x+1=(x^3-x+1)(x^2+x+1)
\(x^5+x^4+1\)
\(=x^3\left(x^2+x+1\right)-x\left(x^2+x+1\right)+\left(x^2+x+1\right)\)
\(=\left(x^3-x+1\right)\left(x^2+x+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có : x5 - x4 + x4 - x3 - x4 + x3 - x2 + x2 - x + x - 1
= x4(x - 1) + x3(x - 1) - x3(x - 1) - x2(x - 1) + x2(x - 1) + (x - 1)
= (x4 + x3 - x3 - x2 + x2 + 1) (x - 1)
= (x4 + 1)(x - 1)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có:
\(x^5+x^4+1\)
\(=x^5+x^4+x^3+1-x^3\)
\(=\left(x^5+x^4+x^3\right)+\left(1^3-x^3\right)\)
\(=x^3\left(x^2+x+1\right)+\left(1-x\right)\left(1+x+x^2\right)\)
\(=\left(x^2+x+1\right)\left(x^3+1-x\right)\)
\(a^5+a^4+1=a^5+a^4+a^3-a^3+a^2-a^2+a-a+1\)
\(=a^5+a^4+a^3-a^3-a^2-a+a^2+a+1\)
\(=\left(a^5+a^4+a^3\right)-\left(a^3+a^2+a\right)-\left(a^2+a+1\right)\)
\(=a^3\left(a^2+a+1\right)-a\left(a^2+a+1\right)+\left(a^2+a+1\right)\)
\(=\left(a^2+a+1\right)\left(a^3-a+1\right)\)
#by_Suho
![](https://rs.olm.vn/images/avt/0.png?1311)
x5 + x4 + 1
= x5 + x4 + x3 - x3 + 1
= x3(x2 + x + 1) - (x3 - 1)
= x3(x2 + x + 1) - (x - 1)(x2 + x + 1)
= (x3 - x + 1)(x2 + x + 1)
![](https://rs.olm.vn/images/avt/0.png?1311)
1 ) \(x^5+x+1\)
\(=\left(x^5-x^2\right)+\left(x^2+x+1\right)\)
\(=x^2\left(x^3-1\right)+\left(x^2+x+1\right)\)
\(=x^2\left(x-1\right)\left(x^2+x+1\right)+\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left(x^3-x^2+1\right)\)
b ) \(x^8+x^4+1\)
\(=\left(x^8+2x^4+1\right)-x^4\)
\(=\left(x^4+1\right)^2-\left(x^2\right)^2\)
\(=\left(x^4-x^2+1\right)\left(x^4+x^2+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
x^5 - x^4 - 1
= x^5 - x^3 - x² - x^4 + x² + x + x^3 - x - 1
= x²( x^3 - x - 1 ) - x( x^3 - x - 1 ) + ( x^3 - x - 1 )
= ( x² - x + 1)( x^3 - x - 1 )
là![](http://mathpic.coccoc.vn/drivermath?render=%24%5Cleft%28x%5E2-x%2B1%5Cright%29%5C%2C%5Cleft%28x%5E3-x-1%5Cright%29%24)